Evaluation of physical, rheological, microbial, and organoleptic properties of meat powder produced by Refractance Window drying. Issue 9 (4th July 2018) - Rostami, Hosein; Dehnad, Danial; Jafari, Seid Mahdi; Tavakoli, Hamid Reza
ABSTRACT: Meat spoils very rapidly and its microbial load exceeds the permitted limit very soon even if it is kept in a refrigerator. The main goal of this study was to dry meat by a Refractance Window drier successfully, for the first time, and to evaluate its compositional, physical, rheological behavior, microbiological, and organoleptic properties. Meat powder produced by RW drying had good physical properties including maximum absolute density of 0.81 g cm −3, porosity of 0.67, rehydration ratio of 2.8, L* value of 64, and minimum a* / b* value of 0.57. Herschel–Bulkley and Bingham models could predict rheological indices of meat powder solutions with high R 2 rates of 0.955–0.995. Sensory evaluation indicated that although meat powder obtained from 3 mm slices was more favorable for panelists, the consistency of 2 mm meat powders was more agreeable, which could be attributed to better functional properties of more dried samples. 100°C and 2 mm treatment could decrease aerobic bacterial count from 6.1 to 3.7 log CFU/g and Enterobacteriaceae population from 3.1 log CFU/g to nil successfully. In summary, our comparison indicated that meat powder produced by Refractance Window drying technique can lead to better dried products than dried meats having been prepared with other novel techniques recently.